2015
DOI: 10.3748/wjg.v21.i8.2504
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir rescue therapy in pregnant females with chronic hepatitis B

Abstract: The use of TDF in pregnant females with chronic HBV and LAM or LdT resistance was safe and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 30 publications
1
22
0
1
Order By: Relevance
“…In the other case, the mother was treated with tenofovir for only 17 days due to non‐compliance with pre‐natal care . Regarding safety, a total of four cases (3.0% [4/134]) of serious adverse events were described in the case series: one case of hypospadias, one case of post‐partum haemorrhage, one case of patent foramen ovale and one case of congenital dislocation of the right knee . However, there were no known foetal deaths after tenofovir treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the other case, the mother was treated with tenofovir for only 17 days due to non‐compliance with pre‐natal care . Regarding safety, a total of four cases (3.0% [4/134]) of serious adverse events were described in the case series: one case of hypospadias, one case of post‐partum haemorrhage, one case of patent foramen ovale and one case of congenital dislocation of the right knee . However, there were no known foetal deaths after tenofovir treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, majority of worldwide guidelines recommend tenofovir as the preferred choice for MTCT prevention in terms of anti‐viral potency, available safety data during pregnancy, and concerns for resistance compared to other anti‐viral agents. To date, a small number of case series and relatively well‐designed non‐randomised controlled trials (NRCT) using tenofovir have been conducted recently . Recently, Pan et al .…”
Section: Introductionmentioning
confidence: 99%
“…It has also extensive experience in HIV settings and therefore a track record of safety in the pregnancy registry. Emerging data and recent data from China and Turkey suggest tenofovir is safe and effective in this setting 56 61 62. In fact, a recent prospective trial from Taiwan involving 118 HBeAg-positive women demonstrated that the tenofovir-exposed infants versus unexposed had much lower HBsAg positivity at 6 months (1.54% vs 10.71%).…”
Section: Hbv Treatment Considerations In Women Of Childbearing Agementioning
confidence: 99%
“…In case of mild disease ( e.g ., no advanced fibrosis, normal ALT levels, viraemia between 2000 UI/mL and 20000 IU/mL), discontinuation of therapy until delivery might be a viable option, as long as an adequate monitoring is carried out to re-start immediately treatment if necessary[ 51 ]. Eventually, another matter of concern is the management of HBV resistance cases: In pregnant women there is limited experience, nonetheless, in gravid subjects experiencing treatment failure (HBV DNA rebound) under LAM or LdT, switching to TDF appears a safe and effective option[ 52 ]. In Figure 2 the current knowledge regarding the treatment of HBV infection in pregnant women is summarized.…”
Section: Hbv Infection In Pregnancy: From the Perspective Of Gravid Wmentioning
confidence: 99%